효율적인 OLED FAB 경유 반송 개선 알고리즘 - 김동소; 최진영 (한국산업경영시스템학회지, 2018)
OLED Display fabrication system is one of the most complicated discrete processing systems in the world. As the glass size grows from 550×650mm to 1,500×1,850mm in recent years, the efficiency of Automated Material Handling System (AMHS) has become very important and OLED glass manufacturers are trying to improve the overall efficiency of AMHS. Aiming to meet the demand for high efficiency of transportation, various kind of approaches have been applied for improving dispatching rules and facility layout, while simultaneously considering the system parameters such as glass cassettes due date, waiting time, and stocker buffer status. However, these works did not suggest the operational policy and conditions of distribution systems, especially for handling unnecessary material flows such as detour. Based on this motivation, in this paper, we proposed an efficient algorithm for improving detour transportation in OLED FAB. Specifically, we considered an OLED FAB simplifying OLED production environment in a Korean company, where four stockers are constructed for the delivery of Lot in a bay and linked to processing equipments. We developed a simulation model using Automod and performed a numerical experiment using real operational data to test the performance of three operation policies under considerations. We showed that a competitive policy for assigning alternative stocker in case of detour was superior to the current dedicated policy using a specified stocker and other considered policies.
Keywords: Detour Transfer; Stocker; Dispatching System; Full Rate; Automod; Simulation